Associations of maternal body composition and nutritional intake with fat content of Indonesian mothers’ breast milk - Ardesy Melizah Kurniati; Diana Sunardi; Ali Sungkar; Saptawati Bardosono; Neng Tine Kartinah (Indonesian Pediatric Society, 2016)
Background Breast milk is the best sole food for infants in their first six months of life. Breast milk fat content accounts for the largest part of infants’ energy and may be influenced by many factors, including maternal factors, which may vary in different settings. So far, there has been no published data about the breast milk fat content of Indonesian mothers, including whether it is affected by their body composition or nutritional intake.Objective To investigate breast milk fat content of Indonesian mothers and its associations with maternal body composition and nutritional intake. Method This cross-sectional study was conducted at Budi Kemuliaan Mothers’ and Children’s Hospital. Breast milk specimens were collected from 48 nursing mothers, centrifuged, and tested by creamatocrit for fat content. A 24-hour food recall was performed to evaluate maternal macronutrient intake. Maternal body composition was evaluated by bioelectric impedance analysis. Univariable correlations between breast milk fat content and either energy and macronutrient intake were assessed using the Spearman rho test.Results All nursing mothers had breast milk fat content within clinically normal range [mean 59.4 (SD 15.9) g/L]. There was no significant correlation between milk fat content and maternal body fat (r = -0.03, P=0.840), total body water (r = 0.09 P=0.509), or muscle mass (r = 0.08, P=0.577). Milk fat content seemed to weakly correlated with maternal fat intake, although it was not statistically significant (r = 0.27, P=0.065).Conclusion Breast milk fat content at one-month post delivery appears not associated with with maternal body composition. It seems to weakly correlate with maternal fat intake but findings need to be confirmed in larger studies with adjustment for confounding variables.